MANIFESTATION OF WILL-POWERED QUALITIES IN THE ACTIVITY OF A PROFESSIONAL PSYCHOLOGIST (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the manifestation of volitional qualities in professional activity, the impact of this process on the professional psychologist's activity, and the results of empirical research on the study of volitional qualities.